A Novel Effect of Bifemelane, a Nootropic Drug, on Intracellular Ca2+ Levels in Rat Cerebral Astrocytes - Yoshitoku Yoshida; Akira Nakane; Mitsuhiro Morita; Yoshihisa Kudo (Elsevier, 2006)
Abstract.: We investigated the effects of bifemelane, a nootropic drug, on the intracellular calcium concentration ([Ca2+]i) in rat cerebral astrocytes using a Ca2+ imaging device. At concentrations of 10 - 30 µM, bifemelane induced a slow onset and small increase in the [Ca2+]i, while at higher concentrations (100 - 300 µM), it induced a rapid transient increase in the [Ca2+]i during administration and a second large increase was seen during drug washout. The first peak was observed in Ca2+-free medium, but its onset was significantly delayed, and no second peak was seen. Neither of these effects was seen in cells treated with thapsigargin, a specific inhibitor of endoplasmic reticulum Ca2+-ATPase, in Ca2+-free medium. When thapsigargin-treated astrocytes were returned to normal medium containing Ca2+ (1.8 mM), the [Ca2+]i increased significantly, and this effect was reversely inhibited by bifemelane. We conclude that bifemelane causes the first peak by stimulating release from intracellular Ca2+ stores and the second by capacitive entry through store-operated Ca2+ channels. Although the detail mechanisms of action of the drug are still unknown, bifemelane will be provided as a pharmacological tool for basic studies on astrocytes. Keywords:: bifemelane, astrocyte, Ca2+, capacitive entry, nootropic drug